Digital Technology Adaptation in Media Industry Management: A Literature Study - Harliantara, Harliantara (Technium: Romanian Journal of Applied Sciences and Technology, 2025)
In recent years, the media industry has undergone a significant transformation owing to the widespread adoption of digital technologies. This study explored the impact of digital technology adaptation on management practices within the media industry. This study examines extant research on how media organisations respond to the challenges and opportunities presented by digital transformation. This review focuses on changes in business models, consumer behaviour, and the utilisation of digital tools for operational and strategic decision making.